2020
DOI: 10.3390/ani10111942
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Eggs from Rosa 1 Hens Fed Diets Containing Seeds of Legume Plants (Lupinus luteus L., Lupinus angustifolius, and Pisum sativum) in Two Laying Phases

Abstract: This study analyzes the eggs’ quality from hens fed with alternative protein to soybean meal (SBM) in relation to laying phase. Here, 226 hens are divided into the control (I) and experimental (II) groups and reared for 50 weeks. There were two feeding phases (weeks 1–36; 37–50). Quality was assessed for 20 eggs from each group. The eggs are analyzed for their external and internal traits. A higher albumen weight in II and higher weights of the components were found in the 37–50 weeks for both groups, also in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
4
1
2
Order By: Relevance
“…Moreover, the HI levels in the present study were probably not high enough to significantly affect the egg yolk colour [4]. Our similar results, namely the similar yolk colour of eggs from hens with free access to the vegetated or unvegetated outdoor area, was probably due to hens in all groups receiving a conventional diet containing ingredients with high pigments [37].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Moreover, the HI levels in the present study were probably not high enough to significantly affect the egg yolk colour [4]. Our similar results, namely the similar yolk colour of eggs from hens with free access to the vegetated or unvegetated outdoor area, was probably due to hens in all groups receiving a conventional diet containing ingredients with high pigments [37].…”
Section: Discussionsupporting
confidence: 61%
“…However, the results regarding egg yolk colour are consistent with those of Yilmaz Dikmen et al [38], who found that the influence of the rearing system on the colour of the yolk was insignificant. These discrepancies may result from the chemical and physical properties of egg yolk, the production cycle of the hens, and the varieties and maturity stage of the herbages used [1,14,37]. Moreover, the HI levels in the present study were probably not high enough to significantly affect the egg yolk colour [4].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Мы полагаем, что в этот период для удешевления рациона оправдано использование гороха, содержание протеина в котором ниже, чем в сое и продуктах ее переработки, принимая во внимание, что пищеварительная система взрослой птицы способна обеспечить хорошее усвоение питательных веществ из комбикормов с горохом. В известных нам публикациях по изучению влияния гороха в рационах в разные продуктивные периоды возраст несушек составлял до 50 нед (17,19,21,22). Сообщения об эффектах комбикормов с горохом на поздних сроках содержания курнесушек родительского стада практически отсутствуют.…”
unclassified
“…Ранее отмечали сходные результаты по сохранению качества инкубационных яиц и выводу цыплят (19), а также при включении 20 % гороха в сочетании с препаратом CELLOVIRIDIN G20X (Россия) (60-70 г/т корма) в комбикорма для мясных кур (17,19). Необходимо отметить, что применение ферментных препаратов позволяет эффективно заменять соевый шрот горохом в рационах кур-несушек, и при этом интенсивность яйцекладки и качество яиц остаются высокими (21,22,31).…”
unclassified